Fulfillment of Rights for Victims of Environmental Pollution Study of the Bengawan Solo River, Kebakkramat District, Karanganyar Regency - Adil Amrulloh; Hanifah Febriani (Proceeding International Conference Restructuring and Transforming Law, 2023)
The aim of this research is to identify the fulfillment of rights for victims of environmental pollution in the Bengawan Solo River Study, Kebakkramat District, Karanganyar Regency. An empirical juridical approach is applied in this research using qualitative methods. This research found that pollution in Kebakkramat District, Karanganyar Regency includes strong odors and agricultural production is not optimal. Apart from that, fulfilling the rights of residents around the river is also limited to assistance, for example in the form of fertilizer. Meanwhile, other needs such as health and compensation were not found.